GC-MS Analysis and Antibacterial Activity of Essential Oils of Five Syzygium Species Leaves - Sunarto Sunarto; Esti Dyah Utami; Nur Amalia Choironi; Muhamad Salman Fareza (ALCHEMY Jurnal Penelitian Kimia, 2023)
The essential oil can inhibit pathogenic bacterial activities, which can be developed to be a natural preservative for food. This research aimed to evaluate the antibacterial activity of the essential oils from five species Syzygium on Bacillus cereus, Escherichia coli, Listeria monocytogenes, Staphylococcus aureus, and Salmonella enterica sv Typhimurium. The research results show that five Syzygium sp. Essential oils have moderate antibacterial properties with a minimum inhibitory concentration (MIC) value of 250 ‒ 500 μg/mL. S. polyanthum essential oils have the highest antibacterial activity than the rest species on B. cereus at 250 μg/mL. Meanwhile, the essential oil of S. polycephalum also showed the highest antibacterial activity with a MIC value of 250 μg/mL against L. monocytogenes. The chemical component analysis using GC-MS shows the main constituents farnesol, nerolidol, and n-decanal, presenting the antibacterial effect.